Reduced graphene oxide multilayers for gas and liquid phases chemical sensing - Gross, Marcos A.; Sales, Maria J. A.; Soler, Maria A. G.; Pereira-da-Silva, Marcelo A. [UNESP]; Silva, Mauro F. P. da; Paterno, Leonardo G. (Royal Soc Chemistry, 2014)
Graphene oxide (GO) multilayers were produced by the layer-by-layer technique after successive immersions of quartz slides into aqueous suspensions of cationic poly(diallyldimethyl ammonium chloride) (PDAC) and anionic GO. The adsorbed amount of GO within the multilayers measured ex situ by UV-vis spectroscopy was found to increase linearly with the number of PDAC-GO bilayers. UV-vis and Raman spectra confirmed the conversion of GO to its reduced form, namely reduced graphene oxide (RGO), when the multilayers were subjected to hot hydrazine. According to AFM images, multilayers are flat with GO sheets forming edge structures. Additionally, impedance spectroscopy provided information regarding the multilayer growth mechanism, which starts with isolated GO sheets that bridge each other after deposition of five PDAC-GO bilayers. As a proof of principle, it was demonstrated that a sensor array composed by reduced multilayers deposited onto interdigitated microelectrodes and interrogated by impedance spectroscopy is capable of discriminating vapours of volatile solvents, including toluene, gasoline, ethanol, chloroform, and acetone, as well as chemicals in aqueous solutions, such as hydrochloric acid, sodium chloride, ammonium hydroxide, and sucrose. This capability was made possible only because the LbL assembly permitted one to tune the sensors' sensitivity with the number of PDAC-GO bilayers. The results presented herein suggest that the reduced PDAC-GO multilayers are promising elements for non-specific chemical sensors.